Growth Regimes in Japan and the United States in the 1990s - Hiroyuki Uni (Revue de la Régulation)
Based on Kaldor’s concept of ‘cumulative causation’, the causes of the economic stagnation in Japan and the high economic growth in the United States in the 1990s are clarified. For this purpose, we formalize mathematically and descriptively two-way routes between labour productivity growth and demand growth; these routes are known as ‘demand regime’ and ‘productivity regime’. Next, we separately estimate these regimes in these two countries, for two periods: the 1980s and the 1990s. According to our estimation, a leftward shift of the demand regime led to the economic stagnation in Japan in the 1990s, and a rightward shift of the demand regime and an increase in the slope of the productivity regime led to the high economic growth in the United States. The causes of these shifts have been empirically clarified.